The Impact of Digital Transformation on Financial Performance : A Case Study of Nike, Inc. - Özbay, Hür Ozan; Machek, Ondřej, 1985-; Jurek, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Digital transformation helped Nike to improve its financials and change the overall strategy to direct-to-consumer. The main research goal is to track the effect of Nike’s digital efforts throughout the years affected the overall financial performance of the company. The research implemented both descriptive financial data analysis and competitor benchmarking between Nike and Adidas. The results suggest that the digital transformation of Nike drives positive effects on financial performance which resulting in improved revenue and net income. This thesis analyzes the digital transformation of Nike and its effect on financial performance.
Vedoucí práce: Ondřej Machek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses